PEMBERIAN BEBERAPA JENIS KOMPOS TERHADAP PERTUMBUHAN BIBIT KARET(Hevea brasiliensis) PADA STUM MINI KLON PB260 DAN AVROS 2037 - Slamat Sandari; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this study was to determine the effect of the type of compost and best clone on the growth of rubber seedlings stum mini clones and clone PB 260 and clone AVROS 2037 and get the kind of good compost for growing rubber trees clones PB 260 and clones AVROS 2037. Research conducted at the experimental field of the Faculty of Agriculture, University of Riau. This study was conducted over four months from February to June 2015. The study was conducted experimentally by using factorial (2 x 3) arranged in Completely Randomized Design (CRD), repeated 3 times. The first factor rubber seedlings V1: Clone PB 260, V2: Clone AVROS 2037, factor II Type B1 compost: Compost Rice Straw dose of 100 g / plant, B2: Compost TKKS dose of 100 g / plant, B3: Compost LCC dose of 150 g / plant. Thus obtained 6 combined treatment and 18 experimental units. So the total number of plants rubber used in this study was 36 seeds. Parameters measured were the length of the shoot, in the number of leaves, stem circumference, root volume, the ratio of crown roots, seeds dry weight. Statistical analysis shows that the interaction of granting the type of compost and rubber seedlings significant effect on the length of the shoot, in the number of leaves, stem circumference, root volume, the ratio of root crown, seedling dry weight in clone PB 260 and clone AVROS 2037 aged 2-6 months. Based on the research that has been done to get the added growth of rubber seedlings and clones of clone PB 260 and clone 2037 AVROS best advised to use compost LCC dose of 150 g / plant. Keywords : Rubber clone PB 260 and clone AVROS 2037, rice straw compost, TKKS and LCC.